(untitled) (Annals of Medical Research, 2021)
Aim: Code Blue intervention is management system that ensure the most rapid and effective resuscitation of a patient in respiratory or cardiac arrest. The aim of the study was to evaluate the current code blue intervention in our hospital and to identify the practical problems associated with functioning of the code blue.Material and Methods: The study population included all patients who code blue had been activated. Data were collected using code blue forms. It was evaluated the age, gender, time to reach the patient, CPR time, the initial rhythm and the results of the application.Results: 188 patients who were given code blue in our hospital in one year were included in the study. The mean age of the patients was 73.4±14.45 years. 55% of the patients were male and 45% were female. The time for the code blue team to arrive was 3.32±1.97 minutes. Cardiopulmonary arrest was not present in 21.80 % of the blue-coded patients, and resuscitation was not required. Percent 78.20 patients were cardiac arrest and resuscitation was performed. The mean administration time of CPR was performed at 28.16±13.36 minutes. The initial rhythms were ventricular tachycardia / ventricular fibrillation (49%), followed by bradycardia (28%) and pulseless electrical activity / asystole (23%). Percent 21.08 patients returned to circulation and 78.19 % patients did not respond. The most common place for code blue was the palliative care unit.Conclusion: The overall survival rate was 21.08 % in the hospital. The code blue application requires repeated education and a periodic assessment of site-specific problems. We concluded that the application of code blue carried out by a trained team is an essential standard in hospitals.Keywords: Code blue; resuscitation; fducation.